2016
DOI: 10.1007/s12274-016-1153-3
|View full text |Cite
|
Sign up to set email alerts
|

Maneuvering charge polarization and transport in 2H-MoS2 for enhanced electrocatalytic hydrogen evolution reaction

Abstract: Semiconducting 2H-MoS 2 with high chemical stability is a promising alternative to the existing electrocatalysts for the hydrogen evolution reaction (HER); however, the HER performance largely suffers from the limited number of active S sites and low mobility for charge transport. In this work, we demonstrate that the limitations of 2H-MoS 2 for the HER can be overcome by forming hybrid structures with metallic nanowires. Taking the integration with Pd as a proofof-concept, we show with solid experimental evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…As demonstrated in Figure c, when the MoS x /CNTs hybrid nanospheres coated on electrode is applied with a negative potential, the electrons transfer process from electrode to CNTs and then to MoS x will be facilitated by the internal electric field, rapidly accumulating an excessive negative charge density on active sites. As a result, the polarized electrons will promote the HER performance in the corresponding electrochemical processes …”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated in Figure c, when the MoS x /CNTs hybrid nanospheres coated on electrode is applied with a negative potential, the electrons transfer process from electrode to CNTs and then to MoS x will be facilitated by the internal electric field, rapidly accumulating an excessive negative charge density on active sites. As a result, the polarized electrons will promote the HER performance in the corresponding electrochemical processes …”
Section: Resultsmentioning
confidence: 99%
“…58 Among them, molybdenum disulfide (MoS 2 ) with a lamellar hexagonal structure similar to graphite has recently emerged as a very promising nonprecious metal HER catalyst with attractive electrochemical performance in acidic electrolytes. 913 Density functional theory (DFT) calculations predict that only the edges of S–Mo–S in the MoS 2 sheets are active for H* adsorption, whereas the basal plane is electrocatalytically inert. 14,15 In addition, it has also been shown that catalysts with moderate hydrogen adsorption have a higher HER activity.…”
Section: Introductionmentioning
confidence: 99%
“…But H ads will continue to consume one electron to complete HER through Heyrovsky step. [38] Therefore, the declined current density can be attributed to hydrogenation of MBE with H ads . Figure 4C shows the I-t curves at a fixed bias in the presence of MBE, and the current densities are positively correlated with the applied bias.…”
Section: Resultsmentioning
confidence: 99%